2021
DOI: 10.7235/hort.20210068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrocooling and 1-MCP Treatment on the Quality Changes of Peach Fruit during Storage

Aditya Nurmalita Pervitasari,
Jong-Hyun Kim,
Kyeongsuk Cho
et al.

Abstract: Author Contributions ANP, J-HK, KC, and SKY prepared all materials and conducted experiments; DK, JK, and D-HK designed the experiments; ANP, DK, DC, and D-HK analyzed the data; JK and D-HK wrote the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Xuan et al [14] found that forced-air precooling improved the storage quality and antioxidant properties of nectarines during storage and transportation. Pervitasari et al [15] found that water-cooled and 1-methylcyclopropene-treated yellow peaches had reduced ethylene production during storage, maintained their hardness and soluble-solids content, and their shelf-life was extended. Caprioli et al [16] found that cold-water precooling reduced the respiration-rate reduction and hardness loss, thereby extending the postharvest storage life of the product.…”
Section: Introductionmentioning
confidence: 99%
“…Xuan et al [14] found that forced-air precooling improved the storage quality and antioxidant properties of nectarines during storage and transportation. Pervitasari et al [15] found that water-cooled and 1-methylcyclopropene-treated yellow peaches had reduced ethylene production during storage, maintained their hardness and soluble-solids content, and their shelf-life was extended. Caprioli et al [16] found that cold-water precooling reduced the respiration-rate reduction and hardness loss, thereby extending the postharvest storage life of the product.…”
Section: Introductionmentioning
confidence: 99%